Preparation and characterization of graphene/polymer nanocomposites - Soah, Jie Miin (2015)
Graphene has been garnering great interest because of its distinctive band structure and impressive physical properties. The challenges to produce graphene in large scale for research and application purposes as well as the drawbacks of various synthesising methods are addressed. A new approach is proposed to prepare high concentration of high quality graphene by direct exfoliation of graphite in aqueous media using alkali lignin (AL) as surfactant. The newly introduced method is simple, effective yet inexpensive and environmental friendly. Monolayer and multi-layer graphene are being successfully exfoliated, clearly displayed by the SEM and TEM images. With optimal dispersing parameters, an aqueous graphene dispersion concentration of 0.65 ± 0.03 mg mL−1 can be reached. Electrostatic repulsion due to adhesion of negatively charged AL on graphene and formation of π–π interaction between them are the underlying principles of nanosheets stabilization mechanism. Finally, mechanical property enhancement due to the inclusion of 0.1wt% graphene filler in epoxy resin is reported, improving the tensile strength, critical stress intensity factor and critical strain energy release rate by 15%, 49%, and 97% respectively.